Communicating Against Crisis: Farmer Group Strategies for Managing Rat Infestation in Yogyakarta’s Rice Fields - Hibban, Ibnu; Fajri , Choirul (Golden Ratio of Social Science and Education, 2025)
This study investigates the interpersonal communication strategies employed by farmer groups in Gemblangan Village, Bantul Regency, Yogyakarta Special Region, to mitigate the severe impact of rat pest (Rattus argentiventer) infestations on rice production. The research aims to answer the following questions: (1) How do farmer groups design and apply interpersonal communication strategies to address rat infestations? (2) What are the outcomes of these strategies for agricultural resilience and social solidarity? Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that the farmer group uses a combination of interpersonal communication practices, including monthly deliberative meetings, group-based WhatsApp communication, and informal interactions in the field. These methods foster participatory dialogue, cultural sensitivity, and mutual understanding among members. The effectiveness of these strategies is demonstrated in reduced crop losses, improved participation in collective pest control, and strengthened social cohesion. This study highlights the limitations of its geographic scope and sample size, which may affect generalizability; however, it contributes to the growing body of literature on agricultural communication by demonstrating how localized interpersonal communication integrates traditional practices with digital tools. Implications extend to communication policies, rural leadership training, and sustainable pest management practices.